Crystallization Kinetics of Hydroxyapatite Nano-films onStainless Steel Through a Sol-Gel Process: Crystallization kinetics of nano-films of hydroxyapatite - Hossein Najafi,; Ziarat Ali Nemati,; Nafiseh Sohrabi,; Zahra Sadeghian, (Iranian Journal of Pharmaceutical Sciences, 2008)
This article describes the preparation and analysis of nano hydroxyapatite (HA) films on stainless steel 316Lthrough sol-gel technique. The process started with preparation of a nitrate and phosphate sol. After aging the sol for 24 h at room temperature a SS316 substrate was dip-coated and heat-treated at 350 to 450 °C fordifferent times in air. The coating phase and structure on substrate were investigated by X-ray diffraction (XRD), fourier transform infrared (FT-IR), differential thermalanalysis (DTA) and scanning electron microscopy (SEM). Degree of crystallinity and time temperature transformation (TTT) diagram of HAfilms obtained with using Avrami equation. Results indicated that HAphase began to crystallize after a heat treatment at 250 °C and the crystallinity increased at a temperature of 450 °C. The HAfilm showed a nano structure with suitable crystallinity after heat treatment.